Ontologische Narratologie Welt erzählen bei Wilhelm Raabe - Pierstorff, Cornelia (Studien zur deutschen Literatur, 2022)
This book writes theory. It looks at the example of the texts written by Wilhelm Raabe between 1856 and 1902 to develop the outlines of an ontological narratology that claims a systematic validity going beyond its historical subject matter. Its starting point is the question: what is world?